The Implementation of Writing Strategies for Enhancing Students’ Writing Competence - Sudirman, Anselmus; Brilyanti, Yashinta Kurnia (English Education Study Program Faculty of Teacher Training and Education, 2024)
Writing strategies are pivotal in enhancing students' writing competence, necessitating a comprehensive and cohesive approach to implement them in diverse instructional contexts. This study examines an all-encompassing framework integrating different writing strategies to improve students’ writing competence, potentially enhancing students' writing skills significantly. It also suggests culturally responsive pedagogical practices that address diverse students’ needs. By thoroughly investigating 16 of 250 previously published articles, the effectiveness of metacognitive strategy-based training can be identified while exploring technological integration, culturally responsive teaching, and self-assessment methodologies. The key findings indicate that metacognitive strategies positively impact students’ writing performance, and they also shed light on the impact of cultural context on writing strategies and their implementations in culturally responsive instructional strategies. Furthermore, self-assessment promotes increased autonomy and self-confidence in identifying students' writing abilities. The study's findings suggest that a comprehensive and cohesive approach, incorporating several methodologies, can more effectively meet students' varying needs and foster enduring enhancements in writing competence. From this perspective, a novel approach is proposed to improve writing instruction in various contexts by addressing limitations in preceding study findings and reexamining them in future studies.